Effectiveness and Strategies Hotel’s Tax Problems in Baubau City - Abidin, Zainul (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
This study attempts to explain the problem of hotel tax in Indonesia especially in Baubau City. With a mixed research design. Sequential explanatory strategy type. To determine the effect of hotel tax effectiveness on local revenue (PAD) in Baubau City, this study used a quantitative design with a survey using a correlation approach. Meanwhile, to find out the strategy to increase hotel taxes using a qualitative design. The results of this study found that only a 2.52% increase in Baubau City's PAD in 2018-2020 was influenced by hotel tax effectiveness. The tax increase strategy carried out both intensification and extensification by the Baubau City BPKAD has many weaknesses so that it has an impact on many obstacles to efforts to increase taxes. No strategy changes have been made to increase hotel tax revenues, including in the face of the COVID-19 pandemic.